The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1111/j.1348-0421.1982.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Enterotoxigenic Escherichia coli in Piglets with Diarrhea in Connection with Feed Changes

Abstract: Twelve weaned piglets (3-week-old) were divided into three groups according to the time of feed change and observed for diarrhea during the time they were 3 to 8 weeks of age. A total of 553 strains of Escherichia coli were isolated from rectal fecal samples and examined for heat-labile (LT) and heat-stable (ST) enterotoxins, pilus antigens (K88, K99, and 987P), hemolysin (Hly), raffinose utilization (Raf) and drug resistance. Enterotoxigenic and/or hemolytic E. coli strains appeared in the rectal feces of 5-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…We previously reported that most of P. multocida isolates in 1979 were antibiotic-susceptible because of poor drug selection pressure in bacteria in respiratory tracts of swine (14) whereas most of Escherichia coli isolates were multiple drug-resistant and R plasmid-bearing (16). However, the present study demonstrated six drug-resistance patterns-Sar, SarCpr, SarSmr, SarSmrCpr, Sar SmrApr, and SarSmrKmrepr in porcine P. multocida isolates from 1982 to 1985.…”
Section: Discussioncontrasting
confidence: 50%
“…We previously reported that most of P. multocida isolates in 1979 were antibiotic-susceptible because of poor drug selection pressure in bacteria in respiratory tracts of swine (14) whereas most of Escherichia coli isolates were multiple drug-resistant and R plasmid-bearing (16). However, the present study demonstrated six drug-resistance patterns-Sar, SarCpr, SarSmr, SarSmrCpr, Sar SmrApr, and SarSmrKmrepr in porcine P. multocida isolates from 1982 to 1985.…”
Section: Discussioncontrasting
confidence: 50%
“…changing from SOYA to DSMP, by decreasing protein availability in the distal small intestine. Shimizu and Terashima (1982) reported increased severity of diarrhoea and appearance of ETEC in 3-week-old pigs when changing from DSMP to soyabean and maize-based diets. However, there was no difference between the number of ETEC excreted in the faeces or in the IL on day 3 post infection of pigs offered the H-DSMP and H-SOYA diets.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that protein availability in the distal part of the small intestine is one of the main factors in determining the level of microbial proliferation and the subsequent risk of PWED (Pluske et al, 2002;Prohá szka and Baron, 1980). In addition, the inclusion of soya bean and maize, at the expense of DSMP, has also been shown to result in increased severity of diarrhoea and the appearance of ETEC in weaner pigs (Shimizu and Terashima, 1982;Miller et al, 1984). The aims of the present work were two-fold.…”
Section: Discussionmentioning
confidence: 99%